Litteratur samt nyudkommen litteratur - Honkasalo, Brynolf; Strahl, Ivar; Waaben, Knud; Johnsen, Jon; Le Maire, Louis; Philip, Allan (Nordisk Tidsskrift for Kriminalvidenskab, 1951)
Book reviews and new litterature